Gut microbiota and metabolomics unveil the mechanisms of Lomatogonium rotatum in ameliorating visceral fat and serum lipids in high-fat diet-induced obese mice - Ji, Xiaoping; Yu, Hongzhen; Wang, Lianqian; Bao, Xuemei; Si, Tegele; Li, Xiaoman; Wang, Hugejiletu; Borjigidai, Almaz; Kusuma Aji, Galih; Bai, Laxinamujila; Fu, Minghai (Frontiers in Pharmacology, 2024)
Lomatogonium rotatum (LR) is a folk medicinal herb traditionally used as a lipid-lowering and antiobesity agent; but its pharmacological mechanism is unclear. In this study, we assessed the alterations of LR on gut microbes and serum metabolites in obese mice and their associated mechanisms of modulation on visceral fat and serum lipid by integrating gut microbiota and metabolomics analyses. Mice were fed a high-fat diet (HFD) to generate obesity and were then given LR and Orlistat orally at different doses (0.18, 0.9, 1.8 g/kg for LR and 0.048 g/kg for Orlistat) for a duration of 9 weeks. The impact of LR on weight loss was assessed through the examination of fat deposition, serum lipid indices, liver indices, and HE pathohistology. The effects of LR on gut microbiota and serum metabolites in obese mice were then investigated by 16S rRNA sequencing technology and untargeted metabolomics, and correlation analysis was performed. LR significantly reduced body weight, feed intake, Lee's index, visceral fat accumulation, serum TG, TC, AST and ALT, and elevated serum HDL levels in obese mice. In addition, 16S rRNA sequencing results indicated that the LR intervention remodeled microbial diversity and composition, increased the relative abundance of gut microbes Bacteroidetes and Porphyromonadaceae in HFD-induced obese mice, and decreased the Deferribacteres, Firmicutes and the Firmicutes/Bacteroidetes ratio.Correlation analyses showed that LR regulation of L-tyrosine and hesperetin metabolism, as well as alterations in the metabolic pathways of Phenylalanine, tyrosine and tryptophan biosynthesis, were associated with the changes in abundance of Bacteroidetes, Firmicutes, Porphyromonadaceae and Deferribacteres. Our study demonstrated that LR has lipid lowering and visceral fat reduction effects and its function may be closely related to the improvement of the gut microbiota and its associated metabolites.